2013
DOI: 10.1021/jm400842x
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1H-Pyrrolo[2,3-b]pyridine Derivative Nortopsentin Analogues: Synthesis and Antitumor Activity in Peritoneal Mesothelioma Experimental Models

Abstract: In this study, we describe the synthesis of new nortopsentin analogues, 1H-pyrrolo[2,3-b]pyridine derivatives and their biological effects in experimental models of diffuse malignant peritoneal mesothelioma (DMPM), a rare and rapidly fatal disease, poorly responsive to conventional therapies. The three most active compounds, 1f (3-[2-(5-fluoro-1-methyl-1H-indol-3-yl)-1,3-thiazol-4-yl]-1H-pyrrolo[2,3-b]pyridine), 3f (3-[2-(1H-indol-3-yl)-1,3-thiazol-4-yl]-1-methyl-1H-pyrrolo[2,3-b]pyridine), and 1l (3-[2-(5-flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 51 publications
0
45
0
Order By: Relevance
“…Compounds containing the pyrrole core have been found to possess antitumoral, antimalarial, antifungal, antibacterial and anti-HIV activity and as such, they represent interesting lead compounds for drug development. [1][2][3][4][5][6] The pharmaceutical potential of pyrrolic compounds is exemplified by the HMG-CoA reductase inhibitor atorvastatin, which has become one of the best-selling pharmaceutical products since its introduction to the global market in 1990. [7][8][9] Pyrrolic compounds continue to enter the pharmaceutical market and include molecules such as the receptor tyrosine kinase inhibitor sunitinib, approved in 2011 for the treatment of advanced neuroendocrine tumours of the pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds containing the pyrrole core have been found to possess antitumoral, antimalarial, antifungal, antibacterial and anti-HIV activity and as such, they represent interesting lead compounds for drug development. [1][2][3][4][5][6] The pharmaceutical potential of pyrrolic compounds is exemplified by the HMG-CoA reductase inhibitor atorvastatin, which has become one of the best-selling pharmaceutical products since its introduction to the global market in 1990. [7][8][9] Pyrrolic compounds continue to enter the pharmaceutical market and include molecules such as the receptor tyrosine kinase inhibitor sunitinib, approved in 2011 for the treatment of advanced neuroendocrine tumours of the pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…Quinoxalinylethylpyridylthioureas (QXPTs) of type 1 and 2 ( Figure 2) represent another class of NNRTIs; many compounds showed a potent activity against both HIV-1 wild-type RT and various HIV-1 mutants HIV-1 RT. 16 Considering the good experience reached in the course of our researches on polycyclic nitrogen systems, bearing pyrrole, [17][18][19][20][21][22][23][24] indole, [25][26][27][28][29][30][31][32][33][34][35] isoindole 36-38 and indazole …”
Section: Introductionmentioning
confidence: 99%
“…Due to the interesting biological activities, different analogues of the marine nortopsentins have been synthesized in which the imidazole moiety of the nortopsentin was replaced by five-or six-membered heterocyclic rings such as thiazole Carbone et al, 2015Carbone et al, , 2013Carbone et al, 2014), pyrazinone (Jiang and Gu, 2000), pyrimidines, pyrazines , thiophenes (Diana et al, 2007a), pyridines , pyrazoles (Diana et al, 2007b) and 1,2,4-thiadiazoles which were reported for their cytotoxicity against several cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%